The Analysis of Affixes in the Novel “Dubliners“ by James Joyce - Andini Pradita (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2022)
The objective of this study was to find the use of affixes in the novel ―Dubliners‖ and to describe the dominantly type of affixes used in the novel ―Dubliners‖. This research took place in the library of Muhammadiyah University of North Sumatera, which is located at Jalan KaptenMuchtarBasri No. 3 Medan. The reason of choosing this place was in terms of fund and time. And there had many books related with the study that can be used as the reference. This study analyzed the affixes in the novel ―Dubliners‖, so the descriptive qualitative method was applied in this research. From the analysis it was found that there were two types of affixes found in the novel of James Joyce. They were prefixes and suffixes, there were 32 Prefixes (16%) and 168 Suffixes (84%) that in the three editions, the Affixes that appeared appeared most frequently in the three editions were suffixes (168 words/84%).